Field Guide to the Trees of the Gila Region of New Mexico - Felger, Richard Stephen (Book collections on Project MUSE., 2021)
Field Guide to the Trees of the Gila Region of New Mexico is the definitive guide for field botanists, researchers, students, and avid nature lovers who wish to explore the natural history of native and introduced tree species across the Gila.